AKTIVITAS MAHASISWA DI CAFÉ WILAYAH KECAMATAN TAMPAN KOTA PEKANBARU - Meiryssa Ditya Putri; Indrawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research was conducted around the Tampan district of Pekanbaru. The aim of the study is to know the initial process of students interested in coming to Cafe around the handsome district of Pekanbaru. Topic focus of this research is to know the activity of students in Cafe Kecamatan Tampan Kota Pekanbaru. The samples in this study amounted to 6 people. The authors use qualitative methods and use sampling techniques purposive sampling. Data instruments are observations, interviews and documentation. From the research done, the authors find. Research finds there are several things that encourage students to do a gathering activity at the cafe. That is as follows: Follow friends, research finds that the influence of peers is very potential to attract students especially the subject of research come to the cafe. Doing college assignments, students or research subjects is no longer focused on old habits where coursework is done at home, cost or in groups at a friend's house. For entertainment, research conducted find all research subjects visiting the cafe with the aim to seek entertainment.  Research also finds there are several student gathering activities in Cafe which are as follows: discussion, research finds that research subjects very often do light discussions about campuses or personal problems in the café around the campus. Filling empty time with chatting, research finds the average research subject spent 2-3 hours to just chat in the café with his colleague. Participate in singing and playing music, research finds there are several research subjects or students who use their own musical instruments when gathered at the cafe. And the rest is to enjoy music that is offered by cafe. Keywords: Gathering, Student, Social Action